Two Types of Modality and Their Expression in Azerbaijani - Sultanzade, Vugar (Yesevi Üniversitesi, 2000)
İn this article the author gives a new classification of tinguistic modality, according to vvhich two kinds of modality are distinguished: obligatory (absoiutive) and facultative (optionai). The obligatory modality is not different from the traditional notion of modality and it is obligatory for ali sentences. The facultative modality appears in such cases where a participant in a situation expresses his/her relation to the corresponding proposition. in the first part of the article the author describes the differences between the mentioned kinds of modality. İn the second part ali means of expressing these types in Azerbaijani are shown on the basis of concrete examples.
The file in this item is the publisher version (published version) of the article.
Keywords: Obligatory Modality; Facultative Modality; Proposition; Modal Frame; Azerbaijani